DEVELOPING ENTERPRISING EDUCATORS: A HYPOTHESIS-DRIVEN APPROACH FOR HIGHER LEARNING FOUNDATIONS - Olufemi Lame (European International Journal of Pedagogics, 2024)
Equipping teachers in higher learning foundations with enterprising capabilities is a concept gaining traction. This paper proposes a hypothesis-driven approach to explore the potential benefits of fostering such capabilities. The research investigates how developing these skills in educators can enhance their effectiveness in the classroom, particularly within the foundational years of higher learning. By testing the hypothesis through a rigorous research design, this study aims to contribute to a deeper understanding of how enterprising educators can positively impact student learning and engagement in higher education.